Le raz de marée irlandais à Montréal - Olson, Sherry; Thornton, Patricia (Les chemins de la migration en Belgique et au Québec: XVIIe-XXe siècles, 1995)
Keywords: Irlandais

Les Irlandais catholiques de Montréal: introduction historique et méthodologique - Slattery, Maureen (Société, culture et religion à Montréal: XIXe-XXe siècle, 1994)
Keywords: Irlandais

Les Irlandais à Montréal. Une présence marquante dès le XIXe siècle - Jolivet, Simon (Montréal en tête, 2013)
Keywords: Irlandais; Saint-Patrick (paroisse)

Les Irlandais catholiques de Montréal : genèse d'une communauté, 1800-1834 - Duchesne, Jonathan (Université du Québec à Montréal, 2021)
Keywords: Famille; Irlandais; Mariage

Les Irlandais et le canal de Lachine. La grève de 1843 - Boily, Raymond (Leméac, 2011)
Keywords: Grèves; Irlandais; Lachine (canal)

L'hostilité entre Irlandais catholiques et Irlandais protestants. La Saint-Barthélemy de Montréal (1853) - Germain, Jean-Claude (Montréal en tête, 2013)
Keywords: Gavazzi, Alessandro; Irlandais; Protestants; Émeutes

Britannique et Irlandaise: l'identité ethnique et démographique des Irlandais protestants et la formation d'une communauté à Montréal, 1834-1860 - Timbers, Wayne (Université McGill, 2001)
Keywords: Britanniques; Irlandais; Protestants

Classe sociale et mobilité résidentielle: le cas des Irlandais à Montréal de 1851 à 1871 / Social Class and Residential Mobility, the Case of the Irish in Montreal 1851 to 1871 - Thach, Quoc Thuy (Université McGill, Département de géographie, 1985)
Keywords: Irlandais; Mobilité résidentielle

Quelques observations sur les mariages irlandais dans la paroisse Notre-Dame de Montréal (1840-1861) - Beaudoin, Philippe (Canadian Ethnic Studies / Études ethniques au Canada, 1998)
Keywords: Irlandais; Mariage; Notre-Dame (paroisse)

Saint-Patrick et les paroissiens irlandais - Olson, Sherry (Les Sulpiciens de Montréal: une histoire de pouvoir et de discrétion, 1657-2007, 2007)
Keywords: Communautés religieuses; Irlandais; Saint-Patrick (église); Sulpiciens; Églises

Trois leaders irlandais au Bas-Canada - Rompré, Mathieu (Cap-aux-Diamants, 2007)
Keywords: Irlandais; O'Callaghan, Edmund B.; Tracey, Daniel; Waller, Jocelyn

Notes sur les relations entre les hospitalières de Montréal et les Irlandais - Kerr, Corinne (L'Hôtel-Dieu de Montréal, 1973)
Keywords: Communautés religieuses; Hospitalières de Saint-Joseph; Hôtel-Dieu; Irlandais

The Challenge of the Irish Catholic Community in Nineteenth-Century Montreal - Olson, Sherry; Thornton, Patricia (Histoire sociale / Social History, 2002)
Keywords: Irlandais

Irish Immigration and the Canadian Church before the Middle of the Nineteenth Century - Cooper, John Irwin (Journal of the Canadian Church Historical Society, 1955)
Keywords: Irlandais

The Irish Migration to Montreal, 1847-1867 - Keep, George Rex (Université McGill, 1948)
Keywords: Irlandais

Montréal aux prises en 1847 avec les victimes de la faim - Desjardins, Édouard (L'Union médicale du Canada, 1970)
Keywords: Irlandais

The Irish Adjustment in Montreal - Keep, George Rex (Canadian Historical Review, 1950)
Keywords: Irlandais

Irish-Catholic Leadership in Nineteenth Century Montreal - Leitch, Gillian (Cahiers d'histoire, 2003)
Keywords: Irlandais

The Irish in the Province of Canada in the Decade Leading to Confederation - Lyne, Daniel Colman (Université McGill, 1960)
Keywords: Irlandais

A Population Takes Flight: The Irish Famine Migration in Boston, Montreal, and Liverpool, and the Politics of Marginalization and Criminalization - Horner, Dan (The Criminalization of Migration: Context and Consequences, 2018)
Keywords: Irlandais

The harp and the shamrock: the two faces of Montreal's Irish community - Bâby, Françoise (The Westmount Historian, 2023)
Keywords: Griffintown; Irlandais

Irish Politics on Parade: The Clergy, National Societies, and St. Patrick's Day Processions in Nineteenth-century Montreal and Toronto - Trigger, Rosalyn (Histoire sociale / Social History, 2004)
Keywords: Irlandais; Processions

Silver and Hotcakes and Beer: Irish Montreal in the 1840s - Olson, Sherry (Canadian Ethnic Studies / Études ethniques au Canada, 2013)
Keywords: Auberges; Irlandais

Origines, richesse et travail / Origins, Wealth and Work - Fyson, Donald; Young, Brian (La famille McCord: une vision passionnée / The McCord Family: A Passionate Vision, 1992)
Keywords: Irlandais; McCord (famille)

Familles montréalaises du XIXe siècle: trois cultures, trois trajectoires - Olson, Sherry; Thornton, Patricia (Cahiers québécois de démographie, 1992)
Keywords: Anglophones; Famille; Irlandais

The Role of the Parish in Fostering Irish-Catholic Identity in Nineteenth-Century Montreal - Trigger, Rosalyn (Université McGill, 1997)
Keywords: Irlandais; Notre-Dame (paroisse)

An Irish heart: how a small immigrant community shaped Canada - Doyle Driedger, Sharon (HarperCollins Publishers, 2011)
Keywords: Griffintown; Irlandais; Quartiers

Solemn Processions and Terrifying Violence: Spectacle, Authority, and Citizenship during the Lachine Canal Strike of 1843 - Horner, Dan (Urban History Review / Revue d'histoire urbaine, 2010)
Keywords: Grèves; Irlandais; Lachine (canal)

The Lachine Strike of 1843 - Pentland, H. C. (Canadian Historical Review, 1948)
Keywords: Grèves; Irlandais; Lachine (canal)

Le 9 juin 1853 à Montréal - Encore l'Affaire Gavazzi - Sylvain, Robert [Philippe] (Revue d'histoire de l'Amérique française, 1960)
Keywords: Gavazzi, Alessandro; Irlandais; Émeutes

The Radicalization of the Montreal Irish: The Role of the "Vindicator" - Jackson, James (The Canadian Journal of Irish Studies, 2005)
Keywords: Irlandais; Rébellions; The Vindicator

Trouble at the Edge of Town: Policing Montreal’s Urban Periphery in the Middle of the Nineteenth Century - Horner, Dan (Micro-Geographies of the Western City, c.1750-1900, 2020)
Keywords: Irlandais; Lachine (canal); Police

Église St. Patrick - Noppen, Luc (Les chemins de la mémoire. Monuments et sites historiques du Québec, 1991)
Keywords: Irlandais; Patrimoine; Saint-Patrick (église)

Anglicans and the Atlantic World: High Churchmen, Evangelicals and the Quebec Connection - Vaudry, Richard W. (McGill-Queen's University Press, 2003)
Keywords: Anglicans; Britanniques; Irlandais; Protestants

Community and Identity in Nineteenth Century Montreal: The Founding of Saint Patrick's Church - Leitch, Gillian I. (Université d'Ottawa, 1999)
Keywords: Irlandais; St. Patrick (église); Églises

The Story of Old St. Patrick's - Lipscombe, Robert (St. Patrick, 1967)
Keywords: Irlandais; St. Patrick (église); Églises

Golden Jubilee of the Reverend Fathers Dowd and Toupin with Historical Sketch of Irish Community of Montreal - Curran, J. J. (Lovell, 1887)
Keywords: Dowd, Patrick; Irlandais; Toupin, Joseph

The Story of One Hundred Years: St. Patrick's Church Montreal, 1847-1947 (s.é., 1947)
Keywords: Irlandais; St. Patrick (église); Églises

L'émeute Gavazzi: violence et liberté d'expression au milieu du XIXe siècle - Breton, Vincent (Bulletin d'histoire politique, 2006)
Keywords: Gavazzi, Alessandro; Irlandais; Protestants; Émeutes

L’émeute Gavazzi: pouvoir et conflit religieux au Québec au milieu du 19e siècle - Breton, Vincent (Université du Québec à Montréal, 2004)
Keywords: Gavazzi, Alessandro; Irlandais; Protestants; Émeutes

Father Patrick Dowd Refuses to Be a Bishop - Berry, Gerald (Canadian Catholic Historical Association Report, 1946)
Keywords: Dowd, Patrick; Irlandais; Saint-Patrick (paroisse)

Prosélytisme et conflits religieux lors de l’épidémie de typhus à Montréal en 1847 - Charest, Maude (Cap-aux-Diamants, 2013)
Keywords: Communautés religieuses; Irlandais; Protestants; Épidémies

Golden Jubilee of St. Patrick's Orphan Asylum - Curran, J. J. (The Catholic Institution for Deaf Mutes, 1902)
Keywords: Irlandais; Orphelinats; St. Patrick's Orphan Asylum

Irish Radicalism and the Roman Catholic Church in Quebec and Ireland, 1833-1834: O'Callaghan and O'Connell Compared - Slattery, Maureen (Canadian Catholic Historical Association, Historical Studies, 1997)
Keywords: Irlandais; O'Callaghan, Edmund B.; Rébellions; Églises

A Rooted Horror: Thomas D'Arcy McGee and Secret Societies, 1845-68 - A. Wilson, David (The Canadian Journal of Irish Studies, 2005)
Keywords: Féniens; Irlandais; McGee, Thomas D'Arcy; Nationalisme

Ethnic Partition of the Work Force in 1840s Montréal - Olson, Sherry (Labour / Le travail, 2004)
Keywords: Anglophones; Britanniques; Français; Irlandais; Protestants; Travail

St. Patrick's and the Irish Catholics - Olson, Sherry (The Sulpicians of Montreal: a history of power and discretion, 1657-2007, 2013)
Keywords: Communautés religieuses; Irlandais; Saint-Patrick (église); Sulpiciens; Églises

Shame upon you as men!: Competing Visions of Masculine Authority in the Aftermath of Montreal's Gavazzi Riot - Horner, Dan (Gender History: Canadian Perspectives, 2014)
Keywords: Britanniques; Canadiens français; Gavazzi, Alessandro; Irlandais; Émeutes

Population, identités sociales et vie quotidienne - Gauvreau, Danielle (Histoire de Montréal et de sa région, 2012)
Keywords: Famille; Femmes; Irlandais; Mortalité; Travail; Veuvage

Population, Social Identities, and Daily Life - Gauvreau, Danielle (Montreal: The History of A North American City, 2018)
Keywords: Famille; Femmes; Irlandais; Mortalité; Travail; Veuvage

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (Études d'histoire du Québec / Studies on the History of Quebec, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."--
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail